2017
DOI: 10.1097/mib.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Distance to Specialist Care and Disease Outcomes in Inflammatory Bowel Disease

Abstract: Introduction Optimal treatment of inflammatory bowel disease requires specialized health care. Patients frequently travel long distances to obtain care for inflammatory bowel disease, which may hinder regular care and affect outcomes adversely. Methods This study included patients with established CD or UC receiving care at a single referral center between January 2005 and August 2016. Distance to our healthcare center from the zip code of residence was determined for each patient and classified into quartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…The other reason could be that patients with lower income or without commercial private insurance cannot afford such expensive but effective biological agents, which resulted in a lower level of remission. This is consistent with that reported previously that travelling long distances to obtain medical treatment for IBD hinders regular care and adversely affects the outcomes—especially increasing the risk of needing IBD-related surgery [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…The other reason could be that patients with lower income or without commercial private insurance cannot afford such expensive but effective biological agents, which resulted in a lower level of remission. This is consistent with that reported previously that travelling long distances to obtain medical treatment for IBD hinders regular care and adversely affects the outcomes—especially increasing the risk of needing IBD-related surgery [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study from the USA found that increased distance of IBD patients’ home to a referral IBD center was associated with increased odds of surgery, biological use, and immunomodulator use. 40 Every increase of 10 miles from the patients’ home to the center resulted in a 9% increase in surgical risk and a 14% increase in the use of biological therapy. 40 Similarly, German patients with IBD were seen less frequently, were prescribed fewer medications, and were less likely to undergo surveillance colonoscopy if they lived in low-density or rural areas.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Every increase of 10 miles from the patients’ home to the center resulted in a 9% increase in surgical risk and a 14% increase in the use of biological therapy. 40 Similarly, German patients with IBD were seen less frequently, were prescribed fewer medications, and were less likely to undergo surveillance colonoscopy if they lived in low-density or rural areas. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Despite effective therapies, a significant proportion of patients have suboptimal short and long-term outcomes. The obstacles for effective treatment outcomes include insufficient monitoring of symptoms, difficulty in getting timely access to a gastroenterologist,[2] and lead time to an effective treatment. [3]…”
Section: Introductionmentioning
confidence: 99%